Norovirus and MS2 inactivation kinetics of UV-A and UV-B with and without TiO2 - Lee, Jung Eun; Ko, GwangPyo (Water research (Oxford), 2013)
Germicidal ultraviolet, such as 254-nm UV-C, is a common method of disinfection of pathogenic enteric viruses. However, the disinfection efficacies of UV-A or -B in terms of inactivating waterborne viruses such as norovirus have not been characterized. We evaluated the inactivation kinetics of MS2 bacteriophage and murine norovirus (MNV), a surrogate of human norovirus (NoV), by UV-A and -B. In addition to UV disinfection, we further investigated whether the presence of TiO2 could enhance the virus inactivation kinetics of UV-A and -B. Both MS2 and MNV were highly resistant to UV-A. However, the addition of TiO2 enhanced the efficacy of UV-A for inactivating these viruses. UV-A dose of 1379 mJ/cm2 resulted in a 4 log10 reduction. In comparison, UV-B alone effectively inactivated both MS2 and MNV, as evidenced by the 4 log10 reduction by 367 mJ/cm2 of UV-B. The addition of TiO2 increased the inactivation of MS2; however, it did not significantly increase the efficacy of UV-B disinfection for inactivating MNV. When these treatments were applied to field water such as groundwater, the results were generally consistent with the laboratory findings. Our results clearly indicated that UV-B is useful for the disinfection of waterborne norovirus. However, MNV was quite resistant to UV-A, and UV-A effectively inactivated the tested viruses only when used in combination with TiO2. [Display omitted] •We evaluated the inactivation kinetics of MS2 and MNV by UV-A and –B with/without TiO2.•UV-A effectively inactivated the tested viruses when used in combination with TiO2.•UV-B alone effectively inactivated both MS2 and MNV.•When these treatments were applied to field water, the results were generally consistent.